PERANCANGAN SISTEM PENDETEKSI JARAK AMAN PARKIR BERBASIS MIKROKONTROLLER ARDUINO - Anthony; Mohammad Fajar; Abdul Munir S (STMIK KHARISMA Makassar, 2018)
This research is aimed to design a system for detecting safe parking distance using Arduino Uno, aspiring to minimize accident risk while parking. Data and information obtained from reviewing literatures about related research and testing the system. Hardware used includes Arduino Uno Board, Camera, TFT LCD Screen (Thin Film Transistor Liquid Crystal Display), Ultrasonic sensor, and a buzzer. Camera and Ultrasonic Sensor placed behind of vehicle which can help user in parking. Picture data obtained from Camera then displayed on TFT LCD which are placed on dashboard. To improve system accuracy, ultrasonic sensor are placed on rear bumper of the vehicle for reading distance which results are displayed to TFT LCD Screen and signals in sound. In result, sensor call still read well distance of the object if the position parallel to the object, when sensor position above object, sensor can read at a certain distance. Position of objects that get closer to the sensor make the level of sensor readings accuracy higher. Moreover in Camera OV7670 testing, Camera still can capture image well in the room that much light, whereas in the room less light images produced blurry.